Copper slag as a catalyst for mercury oxidation in coal combustion flue gas. (April 2018) - Li, Hailong; Zhang, Weilin; Wang, Jun; Yang, Zequn; Li, Liqing; Shih, Kaimin
Highlights: Reducing industrial waste and controlling Hg 0 emission was simultaneously achieved. Copper slag exhibited excellent performance in Hg 0 oxidation from 200 °C to 300 °C. HCl was the flue gas component responsible for Hg 0 oxidation over the copper slag. Iron oxides and copper oxide in the copper slag were active in Hg 0 oxidation by HCl. Hg 0 oxidation over the copper slag followed the Langmuir-Hinshelwood mechanism. Abstract: Copper slag is a byproduct of the pyrometallurgical smelting of copper concentrate. It was used in this study to catalyze elemental mercury (Hg 0 ) oxidation in simulated coal combustion flue gas. The copper slag exhibited excellent catalytic performance in Hg 0 oxidation at temperatures between 200 °C and 300 °C. At the most optimal temperature of 250 °C, a Hg 0 oxidation efficiency of 93.8% was achieved under simulated coal combustion flue gas with both a high Hg 0 concentration and a high gas hourly space velocity of 128, 000 h −1 . Hydrogen chloride (HCl) was the flue gas component responsible for Hg 0 oxidation over the copper slag. The transition metal oxides, including iron oxides and copper oxide in the copper slag, exhibited significant catalytic activities in the surface-mediated oxidation of Hg 0 in the presence of HCl. It is proposed that the Hg 0 oxidation over the copper slag followed the Langmuir-Hinshelwood mechanism whereby reactive chlorine species that originated from HCl reacted with the physically adsorbed Hg 0 to form oxidized mercury. This study demonstrated the possibility of reusing copper slag as a catalyst for Hg 0 oxidation and revealed the mechanisms involved in the process and the key factors in the performance. This knowledge has fundamental importance in simultaneously reducing industrial waste and controlling mercury emissions from coal-fired power plants.